MUSIK KASIDAH DAN PERANNYA DALAM DAKWAH NUSANTARA - Siti Rohbiah, Tatu (Jurnal Bimas Islam, 2015)
Abstract Kasidah is one of Islamic music that made by the friends of Anshor in Madina to welcome the arrival of Rasulullah as their happiness.Before the advent of Islam, the Arabs used this art as art because they are hereditary predilection them in the form of Arabic poetry.Arabiah of the peninsula, to Persia, then to Turkey and eventually to the Nusantara brought the merchants. The next development of this art is used as a media of da?wa in the kingdom of Demak by Walisongo, and is still used as a folk entertainment arts Indonesia. Cultural contiguity between nations experiencing made it acculturation of art. In addition, the times have made this art growing and experiencing innovations, ranging from packaging, display, musical instruments, to the lyrics. However, some kasidah are unchanged from its basic form. There is a traditional kasidah, and there is also a modern kasidah. Both kinds of these kasidah by Muslims of the past until now used as a media of da?wa in the onslaught of Western art that goes into the Nusantara.   Abstraksi Kasidah adalah salah satu kesenian Islam yang dijadikan para sahabat Anshor di Madinah dalam menyambut Rasulullah sebagai bentuk kesenangan. Sebelum kedatangan Islam, kesenian ini dijadikan bangsa Arab sebagai kesenian yang turun-temurun kerena kegemaran mereka pada bentuk puisi Arab.Dari Jazirah Arab, ke Persia, lalu ke Turki dan akhirnya ke Nusantara dibawa para saudagar. Perkembangan berikutnya kesenian ini dijadikan media dakwah di Kerajaan Demak oleh para Walisongo, dan hingga kini masih dijadikan kesenian hiburan rakyat Indonesia.Persentuhan budaya antar bangsa menjadikan kesenian ini mengalami akulturasi seni. Disamping itu, perkembangan zaman telah menjadikan kesenian ini kian berkembang dan mengalami inovasi, mulai dari kemasan, tampilan, alat musik, hingga lirik lagunya. Namun demikian, kasidah ada pula yang tidak mengalami perubahan dari bentuk dasarnya. Ada kasidah tradisional, dan ada pula kasidah modern. Kedua macam kasidah ini oleh umat Islam dari dulu hingga kini dijadikan sebagai media dakwah di tengah gempuran kesenian Barat yang masuk ke Nusantara.